Sodium Butyrate Ameliorates Streptozotocin-Induced Type 1 Diabetes in Mice by Inhibiting the HMGB1 Expression - Guo, Yu; Xiao, Zheng; Wang, Yanan; Yao, Weihua; Liao, Shun; Yu, Bo; Zhang, Jianqiang; Zhang, Yanxiang; Zheng, Bing; Ren, Boxu; Gong, Quan (Frontiers in Endocrinology, 2018)
Type 1 diabetes (T1D) is an autoimmune disease characterized by the immune cell-mediated progressive destruction of pancreatic -cells. High-mobility group box 1 protein (HMGB1) has been recognized as a potential immune mediator to enhance the development of T1D. So we speculated that HMGB1 inhibitors could have anti-diabetic effect. Sodium butyrate is a short fatty acid derivative possessing anti-inflammatory activity by inhibiting HMGB1. In the current study, we evaluated the effects of sodium butyrate in streptozotocin (STZ)-induced T1D mice model. Diabetes was induced by multiple low-dose injections of STZ (40mg/kg/day for 5 consecutive days), and then sodium butyrate (500mg/kg/day) was administered by intraperitoneal injection for 7 consecutive days after STZ treatment. Blood glucose, incidence of diabetes, body weight, pancreatic histopathology, the amounts of CD4+T cell subsets, IL-1β level in serum and pancreatic expressions levels of HMGB1 and NF-κB p65 protein were analyzed. The results showed that sodium butyrate treatment decreased blood glucose and serum IL-1β, improved the islet morphology and decreased inflammatory cell infiltration, restored the unbalanced Th1/Th2 ratio, and down-regulated Th17 to normal level. In addition, sodium butyrate treatment can inhibit the pancreatic HMGB1 and NF-κB p65 protein expression. Therefore, we proposed that sodium butyrate should ameliorate STZ-induced T1D by down-regulating NF-κB mediated inflammatory signal pathway through inhibiting HMGB1.